How Does Digital Finance Affect Carbon Emissions? Evidence from an Emerging Market - Hui Zhao (MDPI AG, 2021)
The existing literature finds that finance has a significant impact on carbon emissions, but there is a lack of theoretical explanation on whether and how digital finance, an important new financial form, affects carbon emissions. This paper uses balanced panel data at the provincial level in China from 2011 to 2018 as a sample to empirically test the relationship between digital finance and carbon emissions and introduces three exogenous events to test the impact of policy shocks. The results show that digital finance has a significant inhibitory effect on carbon emissions; the implementation of the policies of ‘G20 High-Level Principles for Digital Financial Inclusion’, ‘Environmental Protection Tax Law of the People’s Republic of China’, and ‘Interim measures for the management of greenhouse gas voluntary emission reduction’ strengthens the suppression of carbon emissions by digital finance, and the robustness test also supports the protection of digital finance. The research conclusions of this article provide theoretical evidence for understanding the relationship between digital finance and other new financial formats and carbon emissions and provide an empirical basis for policy-makers to promote the development of digital finance to reduce carbon emissions.